Peningkatan Kapasitas Pengusaha Kopi di BTN Gunung Sari Kecamatan Gunung Sari Kabupaten Lombok Barat - Taslim Sjah; Halil Halil; I ketut Budastra; I Gusti Lanang Parta Tanaya (Unram Journal of Community Service, 2022)
Coffee is one of the products consumed by many people, so many coffee businesses are growing everywhere. The coffee business is supposed to be profitable, but sometimes it is less profitable. Coffee produced at BTN Gunung Sari, Gunung Sari District, West Lombok Regency, has several aspects that need to be improved regarding the product and its business management. To obtain greater benefits from the coffee business in this area, it is necessary to increase the capacity of the coffee entrepreneurs in the area, including in coffee processing, product marketing, business management, and other technical capabilities related to the business. This capacity-building activity is carried out through training (lectures, discussions, and practices) on technical, business, and management aspects of the coffee business. Evaluation of the activities showed positive results in the form of increased knowledge and enthusiasm for business because of the potential for increasing profits obtained by applying the knowledge received. Therefore, this kind of activity needs to be carried out again in new locations and in new fields of activity (business). Extension activities like this need to be carried out because they are needed by the business community who foresee emerging business opportunities. This (or other) business opportunity needs to be exploited, among others through increasing knowledge and skills related to the choice of type of business, followed by a 'know-how' for the business.